1821 Me. Laws 98, An Act for the Prevention of Damage by Fire, and the Safe Keeping of Gun Powder, chap. 25, § 1 - (:unkn) unknown (General Publisher, 1821)
Prohibited any person from possessing any gunpowder, in any quantity, unless permitted by local rules and regulations.
--
Keywords: GUN POWDER STORAGE